Assessing the Impact of Medical Malpractice on Healthcare Delivery in Uganda - Gloria Esther Nabakooza (Uganda Christian University, 2024)
Medical malpractice is the legal cause of action that results from a negligent act or omission by a healthcare professional, which deviates from the standards in their profession hence causing injury or death to the patient. According to the Black’s Law Dictionary, medical negligence is defined as a failure to provide medical, dental or psychiatric care that is necessary to prevent or to treat serious physical or emotional injury or illness. Medical malpractice presents a significant challenge to the healthcare sector worldwide, and this affects the recovery of patients, the credibility of healthcare providers and in general, the trust and confidence that the public has in the medical profession. Cases of medical negligence in Uganda have continuously become a rampant occurrence hence causing injury and death. This dissertation is targeting to discover and put to light the effects of medical malpractice in regards healthcare delivery in Uganda, mainly throwing more light on the causes, consequences and likely mitigation ideas/ strategies.